1999
DOI: 10.1677/joe.0.1610041
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor gene and protein: strong expression in thyroiditis and thyroid carcinoma

Abstract: Angiogenesis is implicated in several pathological conditions, such as inflammation and tumor growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
113
3
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 140 publications
(125 citation statements)
references
References 33 publications
(30 reference statements)
6
113
3
3
Order By: Relevance
“…Yet, VEGF overexpression in thyroid tumours appears to be related to some clinical/pathological data of the patients (6 -10). VEGF overexpression correlated with PTC size in adults and children (9), and higher VEGF expression correlated with tumour metastatic behaviour and recurrence (8). In the present report, VEGF staining was found to be significantly more frequent in PTCs than in FTCs or PDTCs.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Yet, VEGF overexpression in thyroid tumours appears to be related to some clinical/pathological data of the patients (6 -10). VEGF overexpression correlated with PTC size in adults and children (9), and higher VEGF expression correlated with tumour metastatic behaviour and recurrence (8). In the present report, VEGF staining was found to be significantly more frequent in PTCs than in FTCs or PDTCs.…”
Section: Discussionsupporting
confidence: 64%
“…Recently, VEGFR expression has been reported in various types of tumour, such as leukaemia (3), pancreatic carcinoma (4) and prostatic carcinoma (5), suggesting a potential autocrine/paracrine VEGF action in these tumours. In thyroid carcinomas, VEGFR expression has been reported mainly in endothelial cells (6,8). However, one study (9) indicated that, besides endothelial cells, VEGFR-1 might also be expressed by PTC cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A common feature of thyroid cancers is their markedly increased vascularization, with an elevated expression of the vascular endothelial growth factor (VEGF) by immunohistochemistry, compared with normal thyroid tissue (Klein et al, 1999;Bauer et al, 2003). VEGF levels are correlated with stage, tumor size, nodal involvement, extra-thyroidal invasion, and distant metastases (Chaplin et al, 1996).…”
Section: Anti-angiogenetic Agentsmentioning
confidence: 99%